Does Sharia-Obedient Status Cause Firms to be Less Involved in Accrual-Based Earnings Management? - Bayu Adi Nugroho; Rizki Annissa; Edhi Juwono; Inung Wijayanti (Binus Business Review, 2019)
The main objective of the research was to investigate the accrual quality of Sharia-obedient firms listed in Indonesia Stock Exchange (IDX). Specifically, this research attempted to study whether Sharia was an effective monitoring mechanism in reducing opportunistic managerial behavior through accrual quality and increasing the accuracy of the accounting report. The accrual quality or accrual truthfulness was measured using two widely-used proxies of accrual-based earnings management. The researchers utilized fixed-effect panel data of 84 manufacturing firms in 2013-2017 or 420 observations for the accrual quality computation and cross-section for the regression models (84 observations). This research also employed Two-Stage Least Squares (2SLS) regression method and Ordinary Least Squares method as the comparison. The researchers find robust results after mitigating heteroscedasticity and endogeneity issues. It shows that Sharia-obedient firms have a significantly higher quality of earnings. It also reveals that the close examination by regulators can improve accounting quality and attract new investors in Islamic market. Hence, the findings of this research may give insights to rule-maker and another accountingrelated department to improve the quality of Islamic or Sharia accounting practices in Indonesia.